2017
DOI: 10.1515/folmed-2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Chronic Treatment with Extracts from Rhodiola Rosea L. and Curcuma Longa L. on the Immunoreactivity of Animals Subjected to a Chronic Mild Stress Model

Abstract: DP. Benefi cial eff ect of chronic treatment with extracts from Rhodiola rosea L. and Curcuma longa L. on the immunoreactivity of animals subjected to a chronic mild stress model. Folia Medica 2017;59(4): 443-53. doi: 10.1515/folmed-2017-0046 Background: Recent studies have suggested increased levels of pro-infl ammatory cytokines in depression. Aim: The present study aimed to evaluate the eff ect of extracts from Rhodiola and Curcuma on immunoreactivity of animals subjected to a chronic mild stress (CMS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
2
17
0
2
Order By: Relevance
“…In our previous set-up chronic administration of the combination of the standardized extracts from R. rosea and C. longa showed beneficial antidepressant-like effects in rats subjected to the CMS model and influenced the immune response following LPS stimulation (Vasileva et al, 2017). Therefore the present study aimed to further clarify the potential antidepressant-like effects of the pure compounds salidroside, curcumin and their combination on the immunoreactivity of animals subjected to the CMS model followed by a LPS-induced inflammation.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In our previous set-up chronic administration of the combination of the standardized extracts from R. rosea and C. longa showed beneficial antidepressant-like effects in rats subjected to the CMS model and influenced the immune response following LPS stimulation (Vasileva et al, 2017). Therefore the present study aimed to further clarify the potential antidepressant-like effects of the pure compounds salidroside, curcumin and their combination on the immunoreactivity of animals subjected to the CMS model followed by a LPS-induced inflammation.…”
Section: Introductionmentioning
confidence: 94%
“…The administration of LPS induces depressive-like behavior in rodents accompanied with an activation of the innate immune response (Kubera et al, 2013;Ohgi et al, 2013). Therefore it could be suggested that CMS model followed by a LPS-challenge would have greater effect on the immunoreactivity of depressed rats (Elgarf et al, 2014;Vasileva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, saliroside upregulates TrkB/BDNF levels and restores 5-HT and NE levels in the prefrontal cortex of LPS-depressed mice compared with the vehicle group [153]. A recent study also evaluated the effects of both single and combined oral administration of R. rosea (250, 500 mg/kg) and Curcuma longa (250, 500 mg/kg) extracts in a CMS mice model of depression followed by LPS-induced inflammation [154]. The combination of R. rosea 500 mg/kg and Curcuma 500 mg/kg remarkably reverses depression-like behavioral changes while providing synergistic anti-inflammatory effects, namely reduced levels of TNF-α and IL-6 in CMS exposed and LPS-challenged mice [154].…”
Section: Inflammation-related Depressionmentioning
confidence: 99%
“…↑neural stem cell proliferation ↑BrdU-positive cells [121]. R. rosea extract (250 and 500 mg/kg) [154] ↓TNF-α and IL-6 in CMS exposed and LPS-challenged mice [154] Potentiated effects when administered with curcuma longa (500 mg/kg) [154]. [139,140] ↓TLR4 via the HMBG1/NF-kb and PI3K/AKT/FoxO1 pathways [139,140].…”
Section: Obstructive Sleep Apnea-and Menopause-related Mood Alterationsmentioning
confidence: 99%
“…Plant adaptogens alleviate the negative effects on health from prolonged exposure to stress, and this is at least in part a result of immunomodulation. Our previous studies found that treatment of stressed rats with extracts from Rhodiola rosea L. and Curcuma longa L. as well as their respective marker substances, salidroside and curcumin, attenuate the production of both IL-6 and TNF-α levels in brain tissue and in serum (Vasileva et al, 2017(Vasileva et al, , 2018. Salidroside has been previously reported to inhibit the pro-inflammatory cytokines' production in depression models (Yang et al, 2014;Zhu et al, 2015).…”
mentioning
confidence: 99%